Produk Usaha Mikro Kecil dan Menengah (UMKM) Berkelanjutan Berbasis Tujuan Pembangunan Berkelanjutan (TPB) di Kejulasi, Agam, Sumatera Barat - Virtuous Setyaka; Apriwan Apriwan; Rifki Dermawan; Reisya Amalia Murfi; Thoriq Giffan Aditya; Andrezal Andrezal (Warta Pengabdian Andalas, 2023)
Micro, Small and Medium Enterprises (MSMEs) as business units in the community's economic activities must survive in the global economy. The demand in the dynamics of the global economy is the presence of sustainable products following the Sustainable Development Goals (SDGs) as a circular economy. It is necessary to strengthen the capacity of MSMEs to produce sustainable products to survive, especially in the global market with a circular economy that is economically and environmentally beneficial. This study and community service was conducted at one of the MSMEs in Agam, West Sumatra, named Kejulasi. Using the literature study method, field observation, and direct dialogue with the business owner, concluded that Kejulasi is still in the process of producing sustainable products. Beyond investment and technology, Kejulasi requires intervention from the government and academia despite the structural barriers arising from international agreements on trade liberalization. In conclusion, a more extensive initiative from the producer and social groups is needed, especially in forming cooperatives, digitalizing cooperatives, and cooperative-based dairy industry ecosystems that enable them to produce sustainable products and survive in the dynamics of the global economy.